Analisis Cilok Terkontaminasi Boraks Menggunakan Spektroskopi Fluoresensi Berbasis High Power UV-LED - Haryarta, Gusfianang; Rakhmadi, Frida Agung; Fajriati, Imelda (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2021)
The analysis research of borax contaminant in cilok using high power UV-LED fluorescence spectroscopy system was successfully done. This study aimed to analyze borax in cilok using a high power UV-LED fluorescence spectroscopy system and to determine its precision and detection limits. The stages of research of borax contaminant in cilok was carried out by preparing tools and materials, sampling, data collection, and data processing. Testing of detection limit was carried out with a variety of borax contaminants of 0% - 40% from 20 grams of cilokandprecisiontestingwasdonebyrepeatingthetestofeachvariation5times. TheresultsshowedthathighpowerUV-LEDfluorescencespectroscopysystemwas used successfully in analyzing cilok contaminated with borax. In addition, the test results showed that the system has precision of 100% and detection limit of2.6%.